2022
DOI: 10.1002/jsfa.11950
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of starch structure and functional properties of tetraploid wheat (Triticum turgidum L.) with differing waxy protein composition

Abstract: BACKGROUND: An increased demand for food has mirrored the increasing global population. Obesity and diabetes are two disorders induced by poor eating choices. Consequently, there is an urgent need to develop modified foods that can ameliorate such illnesses. The objective of this study was to explore the effect of Waxy genes on the structural and functional properties of starch, with the aim of improving food quality. Wild-type tetraploid wheat was compared with three mutants with different Waxy gene combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Starch granule size, shape, composition, and structure of amylose and amylopectin determine the functional properties and end use of starch. [ 35,36 ] Previous studies have reported a negative correlation between starch granule size and starch digestibility. [ 37,38 ] However, recent studies have established that starch granules of smaller sizes are more amenable to enzymatic hydrolysis due to their larger surface area for enzymatic binding and reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Starch granule size, shape, composition, and structure of amylose and amylopectin determine the functional properties and end use of starch. [ 35,36 ] Previous studies have reported a negative correlation between starch granule size and starch digestibility. [ 37,38 ] However, recent studies have established that starch granules of smaller sizes are more amenable to enzymatic hydrolysis due to their larger surface area for enzymatic binding and reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Semolina produced from complete waxy durum wheat was not suitable for making pasta because of its lower firmness, higher cooking loss and increased stickiness compared to durum wheat 53 . Sharma et al .…”
Section: Starch Compositionmentioning
confidence: 99%
“…52 Semolina produced from complete waxy durum wheat was not suitable for making pasta because of its lower firmness, higher cooking loss and increased stickiness compared to durum wheat. 53 Sharma et al 54 reported that partial waxy durum wheat had a minor impact on reducing pasta quality. Although waxy durum is not suitable for making pasta, the softening properties of waxy dough may allow new food applications such as meat analogues for thickening purposes.…”
Section: Starch Compositionmentioning
confidence: 99%